Preparation and in vitro evaluation of Eudragit microspheres containing acetazolamide - (:unkn) unknown (ELSEVIER, 2004)
The aim of this study was to prepare and evaluate Eudragit (RS and RL) microspheres containing acetazolamide. Microspheres were prepared by solvent evaporation method using acetone/liquid paraffin system. The influence of formulation factors (stirring speed, polymer:drug ratio, type of polymer, ratio of the combination of polymers) on particle size, encapsulation efficiency and in vitro release characteristics of the microspheres were investigated. The yields of preparation and the encapsulation efficiencies were high for all formulations the microspheres were obtained. Mean particle size changed by changing the polymer:drug ratio or the stirring speed of the system. Although acetazolamide release rates from Eudragit RS microspheres were very slow and incomplete for all formulations, they were fast from Eudragit RL microspheres. When Eudragit RS was added to Eudragit RL microsphere formulations, release rates slowed down and achieved the release profile suitable for peroral administration. (C) 2003 Elsevier B.V All rights reserved.
Keywords: acetazolamide; Eudragit; microspheres; controlled release; RELEASE; MICROCAPSULES; DESIGN